(In)correct Narratives of the Middle East Cinema - Images, Redakcja (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2024)
Middle Eastern cinema, with its rich cultural heritage and diverse history, is an extremely intriguing and multifaceted area of research. This specific region is a meeting place of a variety of traditions, cultures, and religions, which is reflected in filmmaking. In recent decades, Middle Eastern cinema has experienced dynamic development, gaining international recognition, and becoming a recognizable player in the global film market. With this issue of “Images”, both the authors and the editors were dedicated to analyzing and interpreting films and digital audiovisual forms from the Middle East: those that reflect the current social, political, and cultural reality of the region, as well as those that seek the historical origins of the phenomena which we are currently observing. The first part contains articles by scholars representing different branches of film and media studies, who have undertaken the analysis of Middle Eastern cinema and digital media from multiple perspectives. The texts compiled in this volume provide an interesting look at how filmmakers from the Middle East region use these media to explore significant existential, social and political themes, while creating narratives that cross cultural and geographical boundaries.